Co-movement of real exchange rates in the West African Monetary Zone - Peterson Owusu Junior; Anokye M. Adam; George Tweneboah (Cogent Economics & Finance, 2017)
In three different ways of lead-lag causal relationship, covariance/correlation and coherence, we apply the wavelets analysis via the Continuous Morlet Wavelet Transform to delineate the significant frequency-time domain lead-lag relationships for the West African Monetary Zone member countries for real US dollar exchange rates and their absolute log returns from January 2001 to April 2015. The results indicate that lead-lag associations at different periodicities vary across the countries. No one country comes off as leading conveniently for both real and absolute returns of the exchange rates. Our results corroborate other evidences of non-convergence of exchange rates in the monetary zone, which hinders the eventual implementation of the single currency in the ECOWAS region.
Keywords: 330; wavelets; Morlet wavelet transform; wavelet power spectrum; coherence; correlation